Utility of molecular diagnostic tools in improving personalized dosing of psychiatric drugs. - Jukić, Marin (Archives of Pharmacy, 2022)
Determining the correct dose, with the aim to achieve optimal exposure, is very important in psychiatric clinical practice, since underexposed patients are less likely to respond to treatment and since adverse drug reactions likelihood and severity is increased in overexposed patients. CYP2C19 and CYP2D6 enzymes metabolize majority of psychiatric drugs and their genetic polymorphism determines patient’s metabolic capacity. The aim was to evaluate the clinical utility of therapeutic drug concentration monitoring and preemptive CYP genotyping. Several retrospective and prospective cohorts of patients, with known CYP genotype and drug levels, were analyzed with the aim to evaluate the association between CYP2C19 and CYP2D6 metabolizer categories on drug exposure, efficacy, and tolerability. Based on 4,700 patients, currently available CYP2D6 metabolizer categorization is not correct and it needs revisions. Based on data from 8,379 patients, clinically relevant changes in escitalopram and sertraline exposure are detected in CYP2C19 slow metabolizers, while clinically relevant changes in aripiprazole and risperidone exposure are detected in CYP2D6 slow metabolizers. Under standard dosing, almost a half of patients treated with these four drugs are not exposed to optimal drug levels. Since such a substantial amount of patients is wrongly dosed for these four drugs, therapeutic drug monitoring of blood concentration, appropriate metabolizer categorization, and pre-emptive CYP genotyping can improve treatment outcomes for these drugs.